DEVELOPMENT OF A GUIDED SELF‐HELP (GSH) PROGRAM FOR THE TREATMENT OF MILD‐TO‐MODERATE POSTTRAUMATIC STRESS DISORDER (PTSD). Issue 11 (13th May 2013) - Lewis, Catrin; Roberts, Neil; Vick, Tracey; Bisson, Jonathan I.
<x xml:space="preserve">Abstract</x> Background There is a shortage of suitably qualified therapists able to deliver evidence‐based treatment for posttraumatic stress disorder (PTSD), precluding timely access to intervention. This work aimed to develop an optimally effective, feasible, and acceptable guided self‐help (GSH) program for treatment of the disorder. Methods The study followed Medical Research Council (MRC) guidance for the development of a complex intervention. A prototype GSH program was developed through an initial modeling phase. Systematic reviews of the literature informed a portfolio of up‐to‐date information for key stakeholders to consider and discuss in a series of focus groups and semistructured interviews, which included 10 mental health professionals with expertise in the fields of GSH and/or PTSD, and seven former PTSD sufferers. Data were analyzed through a process of Inductive Thematic Analysis and used to inform the content, delivery, and guidance of a GSH program for PTSD. The prototype was piloted with 19 PTSD sufferers in two pilot studies, and refined on the basis of their quantitative results and qualitative feedback. Results The final version was available online and in hardcopy. It included 11 modules, some being mandatory and others optional, allowing tailoring of the intervention to meet an individual's specific needs. Qualitative and quantitative results of the pilot studies supported its efficacy in terms of reducing traumatic stress symptoms and its acceptability to PTSD sufferers. Conclusions Delivering psychological treatment in a GSH format shows promise as an effective and acceptable way of treating mild‐to‐moderate PTSD.